The PvNF-YA1 and PvNF-YB7 Subunits of the Heterotrimeric NF-Y Transcription Factor Influence Strain Preference in the Phaseolus vulgaris–Rhizobium etli Symbiosis - Rípodas, Carolina; Castaingts, Melisse; Clúa, Joaquín; Villafañe, Julieta; Blanco, Flavio Antonio; Zanetti, María Eugenia (Frontiers in Plant Science, 2019)
Transcription factors of the Nuclear Factor Y (NF-Y) family play essential functions in plant development and plasticity, including the formation of lateral root organs such as lateral root and symbiotic nodules. NF-Ys mediate transcriptional responses by acting as heterotrimers composed of three subunits, NF-YA, NF-YB and NF-YC, which in plants are encoded by relatively large gene families. We have previously shown that, in the Phaseolus vulgaris x Rhizobium etli interaction, the PvNF-YC1 subunit is involved not only in the formation of symbiotic nodules, but also in the preference exhibited by the plant for rhizobial strains that are more efficient and competitive in nodule formation. PvNF-YC1 forms a heterotrimer with the PvNF-YA1 and PvNF-YB7 subunits. Here, we used promoter:reporter fusions to show that both PvNF-YA1 and PvNF-YB7 are expressed in symbiotic nodules. In addition, we report that knock-down of PvNF-YA1 and its close paralog PvNF-YA9 abolished nodule formation by either high or low efficient strains and arrested rhizobial infection. On the other hand, knock-down of PvNF-YB7 only affected the symbiotic outcome of the high efficient interaction, suggesting that other symbiotic NF-YB subunits might be involved in the more general mechanisms of nodule formation. More important, we present functional evidence supporting that both PvNF-YA1 and PvNF-YB7 are part of the mechanisms that allow P. vulgaris plant to discriminate and select those bacterial strains that perform better in nodule formation, most likely by acting in the same heterotrimeric complex that PvNF-YC1.